Peterpan Syndrome Phenomenon : Self-Identity Crisis In Forming Intimation In Adult Man - Diana Putri Arini (PSIKODIMENSIA, 2019)
Peter Pan syndrome is inspired by the popular story of a child who has never grown up from a dream land. The term Peter Pan syndrome is given to men who enter adulthood but behave childish characterized by behavior that refuses social responsibility and difficulty forming commitment in interpersonal relationships. Individuals with Peter Pan syndrome are shown as someone loves fun, brave, likes challenges and has a great view of themselves. On the other hand, individual Peter Pan syndrome has a excessive anxiety forming commitment with others. This paper aims to explain the phenomenon of Peter Pan syndrome that occurs in adult men in a psychosocial perspective. The early adulthood is a phase to be responsible for self, others and the environment. In the early adulthood, social demands and pressures create role confusion, uncertainty about the future and anxieties for responsibility. Anxiety facing adult responsibilities is a form of failure in the task phase of adolescent development. Failure to face developmental tasks in adolescence results in role confusion. This assume to be the cause of unpreparedness to face the task of further development in early adulthood.